2017
DOI: 10.2301/neurosonology.30.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of muscle echogenicities in patients treated with second generation long acting injectable antipsychotics

Abstract: IntroductionAntipsychotic depots or long-acting injections were introduced in the 1960s as a means of improving medication adherence and thereby enhancing desired clinical outcomes 1) . Several first-generation (FG)-long-acting injectable antipsychotics (LAIs) and three second-generation LAIs (SG-LAIs) are currently available for administration into either the gluteal or deltoid muscle. These LAIs are administered by intramuscular (IM) injection. A single injection effect lasts within the range of 1 week to 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As such, the current IM injection method has its limitations, featuring a multitude of problems in terms of ensuring medical safety and establishing a proven IM injection technique. The authors' research team has experience in the use of ultrasound diagnostic devices to conduct analysis of drug luminance changes post-IM injection [17], the relationship between injection site reactions and treatment efficacy according to IM injection needle penetration depth [11], and research involving appropriate and safe needle penetration length in IM injections [15] [18] [19] [20]. Data were obtained from 136 patients undergoing treatment with LAI and 83 healthy subjects by ultrasonogra-T. Tanioka et al phy at four psychiatric hospitals and one psychiatric clinic in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the current IM injection method has its limitations, featuring a multitude of problems in terms of ensuring medical safety and establishing a proven IM injection technique. The authors' research team has experience in the use of ultrasound diagnostic devices to conduct analysis of drug luminance changes post-IM injection [17], the relationship between injection site reactions and treatment efficacy according to IM injection needle penetration depth [11], and research involving appropriate and safe needle penetration length in IM injections [15] [18] [19] [20]. Data were obtained from 136 patients undergoing treatment with LAI and 83 healthy subjects by ultrasonogra-T. Tanioka et al phy at four psychiatric hospitals and one psychiatric clinic in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yasuhara et al 14) suggested that the ultrasonographic findings could be distinguish among RLAI, PLAI and ALAI. The IM LAIs on B-mode scan showed its specific echogenicity in the muscle depending on its physical structures and chemical properties.…”
mentioning
confidence: 99%